Immunogenicity of dupilumab in adult and pediatric patients with atopic dermatitis - Kamal, Mohamed A.; Kosloski, Matthew P.; Lai, Ching-Ha; Partridge, Michael A.; Rajadhyaksha, Manoj; Kanamaluru, Vanaja; Bansal, Ashish; Shabbir, Arsalan; Shumel, Brad; Ardeleanu, Marius; Richards, Susan M.; Yan, Hong; et al. (Frontiers in Immunology, 2024)
Background: Development of anti-drug antibodies (ADAs) and neutralizing antibodies (NAbs) to monoclonal antibodies may adversely impact pharmacokinetics, efficacy, and/or safety.Objective: To describe incidence, titer, and persistence of dupilumab ADAs and NAbs, and their effects on pharmacokinetics, efficacy, and safety in patients with atopic dermatitis (AD).Methods: This analysis included seven phase 3 randomized, placebo-controlled (N=2,992) and two longterm open-label extension (N=2,287) trials of subcutaneous dupilumab in adults and pediatric patients with moderate-to-severe AD. ADA, NAb, and dupilumab concentration in serum were assessed using validated immunoassays. ADA impacts on efficacy (EASI) and safety were assessed.Results: Treatment-emergent ADAs were observed in up to 8.6% (aged ≥18 years), 16.0% (12-17 years), 5.3% (6-11 years), and 2.0% (6 months to 5 years) dupilumab-treated patients. Among dupilumab-treated patients, ≤3.7% had persistent responses, <1% had high titers (≥10,000), and ≤5.1% were NAb-positive. NAbs were more common in patients with moderate-and high-titer ADA responses. High-titer ADAs, while infrequent, were the variable most associated with lower dupilumab concentrations in serum and loss of efficacy, independent of NAb status. Efficacy was generally similar in ADA-positive andnegative patients. For most patients with high-or moderate-titer ADAs, titers decreased and efficacy improved over time with continued dupilumab treatment. ADA-positive and -negative patients had similar incidences of treatment-emergent and serious treatment-emergent adverse events. One patient with high-titer ADAs developed serum sickness.In patients with AD, ADAs and NAbs had minimal impact on dupilumab concentration, efficacy, and safety, except for high-titer ADAs in a small number of patients.